How can modeling responsibly inform decision-making in malaria? - Jaline Gerardin; Melissa A Penny (PLoS Biology)
When models are used to inform decision-making, both their strengths and limitations must be considered. Using malaria as an example, we explain how and why models are limited and offer guidance for ensuring a model is well-suited for its intended purpose.